ELECTROOPTIC CHARACTERISTICS OF COLLOIDAL SILVER SOLUTIONS USING TRANSVERSE ELECTROMAGNETIC MODE OF INCOMING LIGHT - Firdausi, K. Sofjan; Setyoningrum, Aqilatul F.D.; Tiwiyaningsih, Tiwiyaningsih; Rahmawati, Aidah; Richardina, Very; Khumaeni, Ali; Sugito, Heri; Soesanto, Qidir M.B; Azam, Much (BERKALA FISIKA, 2020)
In this paper, we demonstrated new electro-optics characteristics of silver nanoparticle solution (NPP) using  linear  light  polarization.  The  electro-optical  properties  of  NPP  solution  were  obtained  by measuring changes in the polarization of light in the transverse electromagnetic (TEM) mode, in which the  source  light  is  made  linearly  polarized  at  0˚  and  90˚to  the  axis  of  polarizer.  NPP  samples  were obtained by laser ablation method and electro-optical properties were obtained through high voltage DC 0-9 kV with light source from green laser pointer (532 nm). The results showed that colloidal silver solution  in water  at  an angle  mode  of  0˚,  strongly  suspected  to  show  active  Plasmon  resonance at a concentration area of 3-5 ppm, with a peak of polarization at a concentration of 4.6 ppm. In the 90˚ mode, it is assumed that the colloidal silver solution is resonant inactive, the change in polarization is caused  only  by  a  combination  of  natural  polarization  and  electro-optical  polarization.  The  study  of changes in the polarization of light through electro-optical effects on silver solutions is very interesting to  be developed  further  using other  particles,  because  it  can provide  a  more  comprehensive  answer. This method also contributes science to the new  perspective of understanding the interaction of light with matter, especially colloidal silver solutions, and the like.Keywords: Light polarization, electro-optics effect, colloidal silver solution